Educational research in Switzerland since World War II as reflected in its institutions and its themes from recent history to some present issues and some perspectives for the near future - Gretler , Armin (Swiss Journal of Educational Research, 2000)
In the institutional development of educational research in Switzerland since World War II, five important phenomena are identified: 1) the spectacular increase in the number of research institutions between 1965 and 1975 mainly due to the then emerging interest of politicians in educational research (in this place, the accent is put not on university institutions, but on the new research and development units within public administration); 2) the creation of partially market-oriented research institutions within university departments in the nineties; 3) the rapidly growing importance of small and very small private educational R&D-enterprises in the nineties; 4) the restructuring linked to New Public Management of several educational R&D-institutions within cantonal public administration, and 5) the creation of a few institutions enhancing the identity of educational research and the cooperation between research, politics, administration and teaching. The identification of research themes over the last fifty years poses some methodological problems. It seems that there is a rather stable «courant normal» mainly in psycho-pedagogical research and research in didactics; in addition, there are a few themes such as the contribution of education to economic growth and international competitivity, and curriculum research which have been important at the beginning as well as at the end of the observed period. From recent history, the article finally goes over to some present issues and some perspectives for the near future.